2009
DOI: 10.1021/jf901609y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of Aminodeoxyglucose Derivatives against Listeria innocua and Salmonella typhimurium

Abstract: In this study aminodeoxyglucose derivatives were synthesized and evaluated for their antibacterial activity against two food bacteria, Listeria innocua and Salmonella typhimurium . 6-Amino-6-deoxy-alpha-D-methylglucopyranose (GSA-6), 3-amino-3-deoxy-D-glucopyranoside (GSA-3), and beta-D-glucopyranosylamine (GSA-1) were synthesized and concurrently tested with commercially available D-glucosamine (GSA-2) for antibacterial activity. Results obtained from this study showed a pronounced antagonist effect due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…salts of oxidized glycosides with a carboxylic acid, 17e19 on the one hand, and cationic N-alkylated amino-derivatives of sugars on the other. Chemical instability 20,21 limits the application of glycosylamines 22 and their subsequent ammonium ions, 23 which resemble the potentially most easily accessible sugar based cationic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…salts of oxidized glycosides with a carboxylic acid, 17e19 on the one hand, and cationic N-alkylated amino-derivatives of sugars on the other. Chemical instability 20,21 limits the application of glycosylamines 22 and their subsequent ammonium ions, 23 which resemble the potentially most easily accessible sugar based cationic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…The reported literature procedure [9] was employed for converting 1,2:5,6-di-O-isopropylidene-α-Dglucofuranose to the C3 azido sugar (5) (Scheme 1). Reduction of 5 using Pd/C under hydrogen atmosphere followed by N-acetylation of the resultant amine using acetic anhydride/pyridine gave the C3 acetamide (6).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of 1,2:5,6-di-O-isopropylidene-3-deoxy-3-acetamido-α-D-glucofuranose (6) 1,2,5,6-Di-O-isopropylidene-3-deoxy-3-azido-α-D-glucofuranose (5) [9] (0.7 g, 2.46 mmol) and Pd/C (70 mg) were taken in CH 2 Cl 2 (3 mL) and the mixture was stirred at 30°C under H 2 atmosphere for 3 h. Pyridine (0.79 mL) and acetic anhydride (0.46 mL, 4.92 mmol) were then added at 0°C and stirring was continued overnight. The mixture was filtered through celite and washed with MeOH.…”
Section: Methodsmentioning
confidence: 99%
“…A very interesting review summarizes the chitosan MIC values according to recent data found in the literature [68] , indicating that the effectiveness of this aminopolysaccharide is dependent on microbial species. Our group has been published several papers dealing with the bioactive properties of chitosan-based matrices [69][70][71][72] and with the bioactivity of glucosamine derivatives [73][74][75] .…”
Section: Chitosanmentioning
confidence: 99%